Impacts of Internet Usage on the Organization of Small and Medium-sized Enterprises: Case of Manufacturing SMEs in downtown Antananarivo- Madagascar - Henri, Ratojoarivelo Setriniaina; Etienne Stefano Raherimalala; Ranjatson Jean Patrick; Andrianjary Myriam; Ratiarimananjatovo Narindra; Koto-Te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Budapest International Research and Critics University, 2024)
The rise of new Internet technologies represents a significant and compelling advancement on a global scale, exerting a dynamic influence on business management. The ongoing digitization process rapidly transforms the structure of value chains, creating new opportunities to enhance value creation for businesses and institutions at an organizational level. However, the widespread adoption of the Internet presents a challenging landscape for small and medium-sized enterprises, which must navigate significant financial obstacles and market uncertainties. Despite these challenges, the use of the Internet deeply influences the daily environment and social dynamics of SMEs. Our research aims to delve deeper into this impact by analyzing how Internet usage affects the organizational framework of small and medium-sized enterprises. We conducted a survey involving more than 125 manufacturing SMEs between 2021 and 2023 in downtown Antananarivo- Madagascar and its surrounding areas, and we performed statistical analysis on the collected data using SPSS and XLSTAT software.